2022
DOI: 10.3390/medsci10030036
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia and Hyponatremia as Predictors of Complicated Appendicitis

Abstract: Several studies have reported elevated serum bilirubin or reduced serum sodium levels in patients with complicated appendicitis (CA). This study examined the efficacy of hyperbilirubinemia, hyponatremia, and both combined in the preoperative diagnosis of CA. Patients who underwent surgery for acute appendicitis were included in this retrospective review. In total, 247 patients were included in the final analysis. Of these, 36 (14.2%) had early appendicitis, 177 (72.0%) had acute suppurative appendicitis, 32 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In 90% patients of perforated appendicitis there's increased bilirubin levels as reported byGavriilidis et al 5 In another study, hyperbilirubinemia was observed in 48% patients of perforated appendicitis. 7 In the research analysiscarried out by Chaudhary et al, hyperbilirubinemia was noticed in the cases of acute suppurative appendicitis, and was much more elevated in cases of perforated as well as gangrenous appendicitis 12,13 .…”
Section: Discussionmentioning
confidence: 98%
“…In 90% patients of perforated appendicitis there's increased bilirubin levels as reported byGavriilidis et al 5 In another study, hyperbilirubinemia was observed in 48% patients of perforated appendicitis. 7 In the research analysiscarried out by Chaudhary et al, hyperbilirubinemia was noticed in the cases of acute suppurative appendicitis, and was much more elevated in cases of perforated as well as gangrenous appendicitis 12,13 .…”
Section: Discussionmentioning
confidence: 98%
“…Hyponatremia also reflected the severity of the underlying process, although it did not induce specific symptoms and might be overlooked by clinicians [ 46 ]. Of note, Shuaib et al revealed that hyperbilirubinemia and hyponatremia yielded a discriminatory value for the diagnosis of complicated appendicitis [ 47 ]. Thus, T-BIL and serum sodium levels can be considered as adjuvant predictors of poor clinical outcomes in neurolisteriosis in all enrolled subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on markers including laboratory tests, scoring methods for the precise diagnosis of complicated appendicitis. [ 7 , 17 ] The laboratory indicators currently used, such as WBC and CRP are not consistently reliable and their accuracy is questionable. In literature, there have been many studies on various parameters such as serum sodium and bilirubin levels, delta neutrophil index, and NLR that was used for distinguishing complicated appendicitis from uncomplicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there have been many studies on various parameters such as serum sodium and bilirubin levels, delta neutrophil index, and NLR that was used for distinguishing complicated appendicitis from uncomplicated cases. [ 8 , 9 , 17 - 24 ]…”
Section: Discussionmentioning
confidence: 99%